Characteristics and properties of a polysaccharide isolated from Wolfiporia cocos as potential dietary supplement for IBS - Yang, Xuan; Lu, Shun; Feng, Yuhan; Cao, Chongjiang; Zhang, Yanliang; Cheng, Shujie (Frontiers in Nutrition, 2023)
As low FODMAP (Fermentable oligosaccharides, disaccharides, monosaccharides and polyols) diet therapy is recommended for most of Irritable Bowel Syndrome (IBS) patients, the consequent insufficient of dietary fibers (DFs) intake exert an adverse impact on intestinal health. This study extracted a water-insoluble polysaccharide from Wolfiporia cocos (WIP) by alkali-extraction and acid-precipitation method. High performance gel permeation chromatography (HPGPC) analysis of WIP showed a single homogeneous composition and the molecular weight was 8.1×103Da. Based on the findings of Fourier transform infrared (FT-IR) spectrum, WIP was indicated as a kind of pyranose form of sugar with β anomeric configuration. According to the result of UV scanning, WIP contained almost no protein. 1H and 13C Nuclear Magnetic Resonance (NMR) spectra of WIP confirmed that the main chain of WIP was 1,3-β -glucan and the result of X-ray diffraction (XRD) demonstrated the amorphous structure of WIP. The properties related to stability, digestion, viscosity, osmotic activity, adsorption and fermentation were investigated, aimed to explore the feasibility of WIP as a new DF supplement for patients with IBS. In addition to good thermal stability, WIP also has low bioavailability and can reach the colon mostly without being digested. Moreover, the low viscosity and osmotic activity, the high water-swelling and water/oil-holding capacity, fructose adsorption capacity and poor fermentation performance of WIP demonstrated that it is suitable for IBS patients. Based on the 16s rRNA sequencing analysis, it is worth noting that WIP regulates IBS associated gut microbiota effectively, such as the abundance of Lachnospiraceae and Prevotella. These findings provide a theoretical basis for the development of WIP as a dietary supplement for IBS patients with low FODMAP diet therapy.